2020
DOI: 10.1111/1744-1633.12477
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric domestic accidents during COVID‐19 pandemic in Hong Kong

Abstract: Background With school closures and social isolation imposed by the COVID‐19 pandemic, both children and parents in Hong Kong have been forced to stay at home for extended periods of time. Besides the disease itself growing globally, this pandemic has inflicted many other healthcare problems. This study aims to look at the impact of COVID‐19 pandemic on paediatric surgical accidents. Methods A retrospective review of all patients under 18 years of age admitted to a tertiary paediatric surgical unit with accide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
(9 reference statements)
1
4
0
1
Order By: Relevance
“…Thus, the increased rates of domestic accidents could be attributed to the fact that children spent more time at home, and in trying to play and run in a limited space, they were more prone to accidents. Our data were also consistent with a similar study conducted in Hong Kong, where domestic accidents presenting to the Pediatric Emergency Department increased significantly during the COVID-19 lockdown compared to the previous year [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the increased rates of domestic accidents could be attributed to the fact that children spent more time at home, and in trying to play and run in a limited space, they were more prone to accidents. Our data were also consistent with a similar study conducted in Hong Kong, where domestic accidents presenting to the Pediatric Emergency Department increased significantly during the COVID-19 lockdown compared to the previous year [8].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, people may have avoided seeking medical assistance for other diseases in hospitals because of the fear of contracting COVID-19. While some studies have referred to a reduction of adult visits to the emergency department (ED) unit, there are only sporadic studies on the behavior of the pediatric population [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was reported that the proportion of domestic accidents in a tertiary pediatric surgical unit increased during the pandemic compared with two previous years. 13 Also, a study of extremity fractures in children and adults reported an increment of home accidents among injury mechanisms during pandemics. 14 Another main finding of our study was increased percentage of poisoning and FBI during both curfew periods.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de ainda configurar-se uma causa preocupante de morte infantil, o número de mortes relacionadas a causas externas esteve em queda entre 2015 e 2019, com leve aumento no ano de 2020. Essa elevação pode decorrer-se do aumento da exposição das crianças ao ambiente domiciliar durante o confinamento na pandemia pelo novo coronavírus, o que propicia uma maior exposição aos riscos ambientais, ao tempo em que a vigilância pode ter sido diminuída associada ao home office dos familiares, o que coloca os acidentes domésticos como efeito colateral da pandemia (Silva et al, 2020;Bressan et al, 2021) Outros trabalhos também evidenciaram aumento da incidência de acidentes infantis durante a pandemia, não só no Brasil, já que a Academia Nacional de Medicina da França também destacou a elevação da notificação desses agravos no mesmo período (Wong et al, 2021;Sabino & Pinto, 2020).…”
Section: Discussionunclassified